Edukasi Gizi Seimbang pada Remaja melalui Media Interaktif - Erwina Safitri; Septy Handayani; Holif Fitriyah; Ellanda Rima Ervyanna; Baiq Dewi Sukma Septiani; Annisa Nur Mahmudah; Emma Dilla Anannda; Muhammad Alvian Khaironi Zaeni (Yayasan Inspirasi El Burhani, 2026)
Introduction: Nutrition education plays an important role in improving adolescent health as an early preventive effort against future stunting. However, conventional education methods are often perceived as less engaging and less effective in enhancing understanding. Objective: The purpose of this service was to improve adolescents’ nutrition knowledge through an interactive puzzle board based on the “Isi Piringku” concept. Method: This public service was conducted by using an introductory workshop on the “Isi Piringku” concept using posters, followed by a group-based interactive puzzle board activity in Harjomulyo Village, Silo Subdistrict, Jember Regency, involving 30 adolescents. Result: The results showed an increase in adolescents’ nutrition knowledge scores after the activity. Participants also provided positive responses, indicating that the interactive puzzle board was interesting, easy to understand, and enjoyable. Conclusion: The interactive puzzle board based on the “Isi Piringku” concept is an effective and practical educational medium for delivering nutrition education to adolescents and has the potential to support community-based stunting prevention efforts.